Monitoring and quantification of rural urbanisation: Case of Arris and Theniet Elabed, Algeria - Soto Sabrina; Hamouda Abida; Rebah Halim (Glasnik Srpskog Geografskog Društva)
In recent decades, rural agglomerations in the Aurès (Algeria) have undergone an to increasing human pressure and major transformations within an uncontrolled urbanization leading not only to a loss of natural and agricultural areas but an intensive artificialization of ecosystems as well. Regular monitoring of urban growth and updated data of the present state of land use are key steps for any action striving for sustainability in the Aurès region. The main objective of this research is to assess and quantify the spatial growth of two rural communities of the Aurès: Arris and Teniet El Abed during the period 1992 - 2022, through a quantitative approach based on the use of multi- date satellite images and the application of landscape metrics. The results reveal a clear unevenly expansion of the urban fabric, with varying rates depending on the period considered, but a bit faster during the period (2002 - 2013). In addition, it appears that development of the urban patch followed at first a continuous mode of spatial growth, then transitioned to a more scattered and fragmented urban form. The study conclusions are not only useful for developing and implementing national policies and programs, but also for assessing and monitoring progress seeking achievement towards Sustainable Development Goals.